2021
DOI: 10.1186/s40164-021-00224-3
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of clinical, pathological, and genomic characteristics of follicular helper T-cell derived lymphomas

Abstract: Background The 2016 World Health Organization (WHO) classification introduced nodal lymphomas of T follicular helper (Tfh) cell origin, such as angioimmunoblastic T-cell lymphoma (AITL), follicular peripheral T-cell lymphoma (F-PTCL), and nodal peripheral T-cell lymphoma with T follicular helper phenotype (nodal PTCL with TFH phenotype). However, the accurate incidence rate and clinical characteristics of F-PTCL and nodal PTCL with TFH are unstudied. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 35 publications
2
9
0
Order By: Relevance
“…There was a higher frequency of RHOA G17V mutations ( P < .0001) in AITL cases, as was also reported recently by Yoon et al. 21 …”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…There was a higher frequency of RHOA G17V mutations ( P < .0001) in AITL cases, as was also reported recently by Yoon et al. 21 …”
Section: Discussionsupporting
confidence: 88%
“…They were present approximately twice as frequently in AITL cases (34.09%) as in PTCL-TFH (16.66%) but could not be detected in cases of PTCL-NOS. 21,29,30 …”
Section: Discussionmentioning
confidence: 99%
“…48 Angioimmunoblastic T-cell lymphoma (AITL) and peripheral T-cell lymphoma with T follicular helper phenotype (PTCL-Tfh) are a group of complex clinicopathological conditions that arise from the expansion of Tfh cells exhibiting high expression levels of ICOS. [50][51][52][53][54] Targeting ICOS expressed on the surface of Tfh cells has emerged as a promising therapeutic strategy for T-cell lymphomas. In this context, MEDI-570, an anti-ICOS antagonist mAb currently being evaluated in a phase I clinical trial for T-cell lymphomas (NCT02520791), showed promising clinical activity in poorrisk refractory and heavily pretreated AITL.…”
Section: Introductionmentioning
confidence: 99%
“…A subset of AITL also show a range of B-cell proliferations that are typically associated with the Epstein-Barr virus (EBV) 21–23. These histologic findings, however, are notoriously heterogenous and can overlap with those of reactive paracortical hyperplasias, infectious and inflammatory conditions, and other PTCL 1–5,24–28. Extensive immunophenotypic panels together with molecular studies for the T-cell receptor (TCR) and B-cell receptor (BCR) gene rearrangements and mutation profiling may be necessary to arrive at a definitive diagnosis.…”
mentioning
confidence: 99%
“…[21][22][23] These histologic findings, however, are notoriously heterogenous and can overlap with those of reactive paracortical hyperplasias, infectious and inflammatory conditions, and other PTCL. [1][2][3][4][5][24][25][26][27][28] Extensive immunophenotypic panels together with molecular studies for the T-cell receptor (TCR) and B-cell receptor (BCR) gene rearrangements and mutation profiling may be necessary to arrive at a definitive diagnosis. Given the lack of specificity among the range of histologies, establishing a TFH phenotype continues to be a cornerstone in the workup of PTCL.…”
mentioning
confidence: 99%